Rancang bangun media pembelajaran edo (automotif education) berbasis jaringan online terintegrasi dengan operasi android pada mata kuliah teknologi motor bensin - Dwi Jatmoko; Pebri Untoro; Aci Primartadi; Joko Purwanto; Yosep Efendi (Universitas Sarjanawiyata Tamansiswa, 2022)
Design of Online Network-Based Online Learning Media Automotive Education which is integrated with Android operation in Gasoline Motor Technology Course in Automotive Engineering Education, University of Muhammadiyah Purworejo. The objectives of this study are (1) to apply an online network-based EDO (Automotive Education) application model that is integrated with android operation as a learning medium in the right Gasoline Motor Technology course for students of Automotive Engineering Education at Muhammadiyah University of Purworejo, (2 ) To find out the feasibility of learning media using an online network-based Automotive Education application that is integrated with android operation on the subject of Gasoline Motor Technology at the Automotive Engineering Education University of Muhammadiyah Purworejo. The type of research used is R&D (Research and Development) with a waterfall path at the development stage. The subjects of this study were second semester students of Automotive Engineering Education, University of Muhammadiyah Purworejo, small group trial, namely class A, which consisted of 5 students and large class trial, namely class B, totaling 20 students. Data collection is done by using the questionnaire method. After the data was obtained, it was analyzed using data analysis techniques. From the results of this research and development, it can be concluded as follows: (1) The creation of an online network-based edo learning media development application product (automotive education) in the learning of Gasoline Motor Technology courses in the cooling system for students of automotive engineering education at Muhammadiyah University Purworejo, (2) The online network-based Edo learning media (automotive education) integrated with android operation is